Answer:
Step-by-step explanation:
Hope this helps :D
Answer:
(-1/3, 3/4)
Step-by-step explanation:
9x + 8y = 3
6x - 12y = -11
Let's solve the system by eliminating x. We need the coefficients of x to be additive inverses, so they will add to zero eliminating x. The LCM of 9 and 6 is 18. Let's multiply both sides of the first by 2 and both sides of the second equation by -3.
18x + 16y = 6
-18x + 36y = 33
The coefficients of x are 18 and -18, which add to zero. Now we add these two equations.
52y = 39
y = 39/52
y = 3/4
Now we substitute y with 3/4 in the first equation and solve for x.
9x + 8y = 3
9x + 8(3/4) = 3
9x + 6 = 3
9x = -3
x = -3/9
x = -1/3
Solution: (-1/3, 3/4)
Answer:
why
Step-by-step explanation:
x = 8
Solution:
Side-splitter theorem:
<em>If a line is parallel to one side of a triangle and the line intersects the other two sides, then this line divides those two sides proportionally.</em>

Do cross multiplication, we get
⇒ 4 × 42 = 21x
Divide by 21 on both sides, we get
⇒ 4 × 2 = x
⇒ 8 = x
Switch the sides.
⇒ x = 8
The value of x is 8.
Answer:
It’s the third ans
Step-by-step explanation: